PLANO DE AÇÃO PARA O TÉCNICO EM ASSUNTOS EDUCACIONAIS EM UMA INSTITUIÇÃO FEDERAL DE ENSINO SUPERIOR - Sanseverino, Adriana Manzolillo (2015)
The present study aims to prepare an Action Plan for Technicians in Educational Issues, in order to guide their practice and to define their role at the Institute of Education of Angra dos Reis, an educational unit of Federal Fluminense University. Technician in Educational Issues is a university position that requires a degree in Pedagogy or in any graduate diploma in Teaching. This professional should be able to plan education related activities, to supervise undergraduate students as well as pedagogic projects, to write outreach and research proposals, among others. However, technicians in educational issues have been performing administrative functions only. In this way, this study intends to show how this professional in education can contribute with teaching, research and outreach activities. Thus, the theoretical framework of the study consists of following themes: People Management, University and Specialists in Education. An extensive literature review and action research were performed. Data collection was obtained by applying a questionnaire to Technicians in Educational Issues of Federal Fluminense University and also by interviewing managers of the Institute of Education of Angra dos Reis. All information was used in the last stage of this research the development of the Action Plan. The reflection proposed by this study may contribute to a new understanding of the role of Technicians in Educational Issues in the university by showing how their background in education can be used in a broader setting. This study can be used as a model to other Action Plans at Federal Fluminense University, as well as in other universities, in order to benefit from the knowledge of these Technicians and to avoid function deviation